Answer:
(6,1)
Step-by-step explanation:
To find the points of inflection, we need to find where the second derivative is equal to zero, or does not exist.
I will take the derivative using the chain rule.
![f(x) = 5\sqrt[3]{(x-6) } + 1 \\\\f(x) = 5(x-6)^{\frac{1}{3} } + 1](https://tex.z-dn.net/?f=f%28x%29%20%3D%205%5Csqrt%5B3%5D%7B%28x-6%29%20%7D%20%2B%201%20%5C%5C%5C%5Cf%28x%29%20%3D%205%28x-6%29%5E%7B%5Cfrac%7B1%7D%7B3%7D%20%7D%20%20%2B%201)
The first derivative:
![f'(x) = 5*\frac{1}{3} (x-6)^{-2/3} \\\\f'(x) = \frac{5}{3} (x-6)^{-2/3} \\](https://tex.z-dn.net/?f=f%27%28x%29%20%3D%205%2A%5Cfrac%7B1%7D%7B3%7D%20%28x-6%29%5E%7B-2%2F3%7D%20%5C%5C%5C%5Cf%27%28x%29%20%3D%20%5Cfrac%7B5%7D%7B3%7D%20%28x-6%29%5E%7B-2%2F3%7D%20%5C%5C)
The second derivative:
![f'(x) = \frac{5}{3} (x-6)^{-2/3} \\\\f''(x) = \frac{5}{3}*-\frac{2}{3} (x-6)^{-5/3}\\\\ f''(x) = -\frac{10}{9} (x-6)^{-5/3}](https://tex.z-dn.net/?f=f%27%28x%29%20%3D%20%5Cfrac%7B5%7D%7B3%7D%20%28x-6%29%5E%7B-2%2F3%7D%20%5C%5C%5C%5Cf%27%27%28x%29%20%3D%20%5Cfrac%7B5%7D%7B3%7D%2A-%5Cfrac%7B2%7D%7B3%7D%20%28x-6%29%5E%7B-5%2F3%7D%5C%5C%5C%5C%20f%27%27%28x%29%20%3D%20-%5Cfrac%7B10%7D%7B9%7D%20%28x-6%29%5E%7B-5%2F3%7D)
Now to find the inflection points we have to find where the second derivative is equal to zero, or do not exist.
![f''(x) = -\frac{10}{9} (x-6)^{-5/3}\\0= -\frac{10}{9} (x-6)^{-5/3}\\0= (x-6)^{-5/3}\\\\](https://tex.z-dn.net/?f=f%27%27%28x%29%20%3D%20-%5Cfrac%7B10%7D%7B9%7D%20%28x-6%29%5E%7B-5%2F3%7D%5C%5C0%3D%20-%5Cfrac%7B10%7D%7B9%7D%20%28x-6%29%5E%7B-5%2F3%7D%5C%5C0%3D%20%28x-6%29%5E%7B-5%2F3%7D%5C%5C%5C%5C)
We can see that the second derivative does not exist when x=6, so there is an inflection point there.
We can solve the original equation to find the coordinate for x = 6.
f(x) = 5∛(x-6) + 1
f(6) = 5∛(6-6) + 1
f(6) = 1
So there is an inflection point at (6,1)